Digital piracy: the issue of knowledge of the institution of copyright law - Czetwertyński, Sławomir (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: The motivation for considering the familiarity of Polish people with copyright law came from previous studies signalling that familiarity to possibly be low. If this conjecture proves true, it will affect the correct interpretation of what digital piracy is by Poles. This, in turn, can lead to problems in designing surveys to measure digital piracy. Aim: The article adopted two research objectives. The first is factual, the second methodical. The first objective is to try to confirm the claim of low knowledge of the institution of copyright law among Poles. The second objective is to try to establish the usefulness of the heuristic Importance Index and the method of clustering similar averages for determining significant differences in the distributions of the evaluations of illegality regarding the forms of copying due to demographic characteristics. Results: As a result, the survey showed that the claim that Poles demonstrate low level of knowledge regarding the copyright law is valid. While not all situations involving the copying of information goods are interpreted incorrectly, the public is overwhelmingly unable to determine whether particular forms of copying are legal or illegal. The study also found that the social group that most harshly labels particular forms of copying as illegal are those with a university education. At the same time, their harsh judgment does not mean that they correctly interpreted the forms of copying in question as illegal.